2023
DOI: 10.1002/ctm2.1170
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil, neutrophil extracellular traps and endothelial cell dysfunction in sepsis

Abstract: Sepsis is a persistent systemic inflammatory condition involving multiple organ failures resulting from a dysregulated immune response to infection, and one of the hallmarks of sepsis is endothelial dysfunction. During its progression, neutrophils are the first line of innate immune defence against infection. Aside from traditional mechanisms, such as phagocytosis or the release of inflammatory cytokines, reactive oxygen species and other antibacterial substances, activated neutrophils also release web‐like st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 204 publications
0
64
0
1
Order By: Relevance
“…Sepsis is identified as life‐threatening organ dysfunction and leads to high mortality 19,20 . Our previous study found that STING is involved in sepsis‐related organ dysfunction and systemic inflammation 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis is identified as life‐threatening organ dysfunction and leads to high mortality 19,20 . Our previous study found that STING is involved in sepsis‐related organ dysfunction and systemic inflammation 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Sepsis is identified as life-threatening organ dysfunction and leads to high mortality. 19,20 Our previous study found that STING is involved in sepsis-related organ dysfunction and systemic inflammation. 8 In this study, we also found that RIPK1 and RIPK3, which are key proteins involved in necroptosis, were significantly upregulated in patients with sepsis and septic shock (Figures 8A and D).…”
Section: Inhibition Of Necroptotic Signalling Protects Against Sepsis...mentioning
confidence: 99%
“…However, NET components can also serve as DAMPs, which may induce a persistent inflammatory response and tissue damage 40 . According to our previous study, NETs aggravated systemic inflammation via the release of TNF‐1α, IL‐1β and IL‐6, 26 and such inflammatory cytokines could further induce NET formation, forming a vicious circle 41 . NETs can also interact with platelets, triggering extensive ‘immunothrombosis’ 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cell adhesion molecules bind to leukocytes, thereby activating them and leading to their infiltration into the underlying tissues ( 54 ). Activated leukocytes not only block microvessels, but also cause an increase in the vascular permeability ( 55 ). Compared with those in control mice, the levels of the plasma pro-inflammatory factors, IL-6 and TNF-α, were found to be significantly increased following lipid emulsion infusion.…”
Section: Discussionmentioning
confidence: 99%